The first record of Astichus Förster (Hymenoptera: Eulophidae: Entiinae), parasitoids of Ciidae (Coleoptera) in bracket fungi, from the Afrotropical Region and the description of four new species from South Africa - Neser, Ottilie C. (Zootaxa, 2012)
The genus Astichus Förster (Eulophidae: Entiinae) is recorded for the first time from sub-Saharan Africa and four newspecies are described from South Africa: A. micans n. sp., A. silvani n. sp., A. gracilis n. sp. and A. naiadis n. sp. .Astichusspecies are known as parasitoids of Ciidae (Coleoptera) tunnelling and living in bracket fungi. The South African speciesemerged together with Ciidae from a variety of bracket fungi from many localities in the region. They are easily separatedfrom known Astichus species from other regions in the world by their distinctive colour and patterning. A key to the SouthAfrican Astichus species, distribution maps, and notes on biology are included, as well as identifications of Ciidae and bracket fungus specimens encountered in the study.